THE PERCEPTION OF BRAZILIAN SOCIETY ABOUT PUBLIC GOVERNANCE OF THE ENVIRONMENT - Endres Palmerston, Sheila Cristina; Garro, Francisco Leonardo Tejerina; Caixeta, Leonardo Rodrigues (CIPEEX, 2022)
THE STUDY INTENDS TO ANALYZE THE APPLICABILITY OF STRUCTURAL DECISIONS TO CASES OF UNCONSTITUTIONAL ENVIRONMENTAL STATE OF AFFAIRS, THE PERCEPTION OF BRAZILIAN SOCIETY ABOUT ENVIRONMENTAL CONFLICTS AND ITS SENSE OF JUSTICE. THE SIMPLE JUDICIAL IMPOSITION THAT THE STATE FULFILLS ITS OBLIGATION TO PROTECT THE RIGHT TO A BALANCED ENVIRONMENT IS NOT ENOUGH FOR IT TO BE EFFECTIVE, DUE TO THE DYSFUNCTIONALITY OF SEVERAL PUBLIC AGENCIES. USING DATA FROM RANDOM SAMPLES OF RESPONDENTS IN BRAZIL, FROM 1995 TO 2020, OF THE CORPORACIÓN LATINOBARÓMETRO, THE BRAZILIAN NATIONAL COUNCIL OF JUSTICE AND THE WORLD VALUES SURVEY DATABASE, IT IS INTENDED TO MEASURE THE INFLUENCE OF BRAZILIANS’ TRUST IN THE POLICY (INDEPENDENT VARIABLE X1), THE JUSTICE SYSTEM (X2), PARLIAMENT (X3) AND GOVERNMENT (X4), CONSIDERING THEIR CONVICTION IN EFFECTIVE ENVIRONMENTAL PROTECTION (DEPENDENT VARIABLE Y). THE DATA WERE SUBMITTED TO A REGRESSION ANALYSIS (HYPERPLANE TYPE PREDICTION MODEL) BETWEEN THE INDEPENDENT VARIABLES (X1, X2, X3, X4) AND THE DEPENDENT VARIABLE (Y), CONSIDERING THE COEFFICIENT OF DETERMINATION TO EXPLAIN THE MODEL ( R²), FOLLOWED BY A PEARSON CORRELATION ANALYSIS (R). THERE WAS A DEGREE OF POSITIVE ASSOCIATION BETWEEN THE INDEPENDENT VARIABLES X1, X2, X3, X4 AND Y. THE COEFFICIENT OF DETERMINATION SHOWED THAT THE MODEL DOES NOT FIT WELL IN RELATION TO THE VARIABLE X1 (R²=2 .94%), BUT YES, IN RELATION TO X2 (R²=94.94%), X3 (R²=96.11%) AND X4 (R²=61.36%). THE RESULTS SHOW THAT THE VARIABLES MOST CORRELATED TO TRUST IN ENVIRONMENTAL PROTECTION ARE X2 (JUDICIARY) AND X3 (PARLIAMENT). THIS SUGGESTS THAT, IN THE PERCEPTION OF BRAZILIAN SOCIETY, TRUST IN JUSTICE AND IN PARLIAMENT ARE THE VARIABLES THAT MOST INFLUENCE THE CONVICTION OF THE SOLUTION OF ENVIRONMENTAL CONFLICTS.